2014
DOI: 10.1166/jbn.2014.1856
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biocompatibility of Poly(lactic-co-glycolic acid) and Poly-L-Lactic Acid Blended with Nanoparticulate Amorphous Calcium Phosphate in Vascular Stent Applications

Abstract: Biodegradable polymers used as vascular stent coatings and stent platforms encounter a major challenge: biocompatibility in vivo, which plays an important role in in-stent restenosis (ISR). Co-formulating amorphous calcium phosphate (ACP) into poly(lactic-co-glycolic acid) (PLGA) or poly-L-lactic acid (PLLA) was investigated to address the issue. For stent coating applications, metal stents were coated with polyethylene-co-vinyl acetate/poly-n-butyl methacrylate (PEVA/PBMA), PLGA or PLGA/ACP composites, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Moreover, it offers excellent bioactivity (low/no cytotoxicity) and the ability to neutralize acidic metabolites resulted from hydrolytic degradation of PLLA. 13 In our earlier studies, 14 ACP was demonstrated to significantly increase the biocompatibility of PLGA as a stent coating layer in a rat aorta stenting model. The metal stents coated with PLGA/ACP composite expedited reendothelialization process, helping endothelial cell migration to cover the injured rat arterial wall.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, it offers excellent bioactivity (low/no cytotoxicity) and the ability to neutralize acidic metabolites resulted from hydrolytic degradation of PLLA. 13 In our earlier studies, 14 ACP was demonstrated to significantly increase the biocompatibility of PLGA as a stent coating layer in a rat aorta stenting model. The metal stents coated with PLGA/ACP composite expedited reendothelialization process, helping endothelial cell migration to cover the injured rat arterial wall.…”
Section: Introductionmentioning
confidence: 91%
“…Each stent was then surface-coated with a layer of paclitaxel in PLGA/ACP (∼ 20 m thickness) as described in our previous report. 14 15 Paclitaxel doses in-strut and on-surface for both stents were presented in Table I. By design, paclitaxel was released from the surface and from within the PowerStent ® Absorb as a function of biodegradation.…”
Section: Stent Design and Fabrication Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed previously, the possible mechanisms of ACP-related increase in PLLA's mechanical properties include restricting its chain mobility, promoting its dimensional stability and increasing the PLLA/ACP composite crystallinity during the degradation process. [14][15][16][17] Since the radial strength is a function of the polymer molecular weight and crystallinity, 27 28 a stent with increased crystallinity would be predicted to have a greater radial strength. In addition, the stent was designed as a unique dual ring structure which also helps to improve radial strength.…”
Section: Sufficient Radial Strength Of the Powerstent ® Absorb Stentmentioning
confidence: 99%
“…[14][15][16][17][18] Our most recent study in porcine coronary artery also demonstrated that the stent had increased structural stability and excellent antirestenotic property one month post-implantation. 19 In the present study, we further evaluate this novel biodegradable DES with respect to the radial strength, biocompatibility and functionality in a porcine model of coronary artery stenting with 6-month follow-up results available.…”
Section: Introductionmentioning
confidence: 99%